The Effectiveness of Green Betel Leaf Decoction on Perineal Wounds Healing in The Work Area of The Puskesmas Siak Hulu II, Kampar Regency - Ary Oktora Sri Rahayu; Fera Z (Institute of Computer Science (IOCS), 2021)
Health Center Working Area, all maternity in the work area of the puskesmas Siak Hulu Public Health Center II Working Area have never been treated with green betel leaves, so far the pharmacological treatment of perineal wounds is using iodine with a healing period of 7-14 days. The purpose of this study was to determine the effectiveness of using green betel water stew on healing perineal wounds in the working area of ​​ the puskesmas Siak Hulu II Health Center. This type of research is quantitative with a quasy experiment design and research design Pretest-Posttest one group design. The study was conducted in January-July 2019. The population in this study 122 people in the work Area of the Puskesmas Siak Hulu II Health Center in Kampar Regency with a total sample of 16 people using Purposive Sampling techniques. The results of this study are that the majority of respondents before being given green betel water decoction experienced poor perineal wounds as much as 81.2%, the majority of respondents after being given green betel water decoction experienced poor perineal wounds as much as 81.2%. Bivariate results, namely the effectiveness of green betel water stew on the healing of perineal wounds in the Work Area of ​​the Puskesmas Siak Hulu II Health Center in Kampar Regency (p = 0,000). The suggestion is that health workers can practice and teach this technique to mothers to accelerate the healing of perineal wounds and the results of this study can be an innovation and alternative treatment option naturally for the health center.